Balochistan before Independence and its Merger with Pakistan - Ali, Mumtaz (Hanken, 2016)
Balochistan has an old history and It has witnessed different ups and down. Since ancient times different invaders have invaded Balochistan in different times. Balochistan remained a tribal society even today; as a result of tribal society it faces different socio- economic and political conflicts. This article will explore and analyzed the history of first Baloch confederacy, tribal and political system of Balochistan. In 12th century the first Baloch confederacy was established in the existing territory of Balochistan by Mir Jalal Han (Khan). Later on Miro Kambarani made it second confederacy and lastly Naseer Khan Noori shaped it administration on the pattern of Baloch tribal confederacy. When Pakistan came into being on 14th August 1947, Balochistan was merged in it on 28th March 1948.